(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2011)
Alzheimer disease (AD) is the most common form of the dementia which occurs among older people above the age of 60 years. The Alzheimer’s disease once considered a rare disorder and it is now seen as a major public health problem that is seriously affecting millions of older people and their families world over. The incidence of AD ranges from 1 to 4 percent of the population per year rising from its lowest level at ages 65 to 70 years to rates that may approach 6 percent for those over the age of 85 years. Alzheimer's is characterised by massive loss of neurons and disrupted signaling between cells in the brain. The disease can be diagnosed post mortem by observing tangles inside and senile plaques outside cells throughout the brain. The major component of the plaques is a small, 40- or 42-amino acid peptide: amyloid beta (Aβ,). Aβ, causative agent in Alzheimer's, was first suggested as the amyloid hypothesis about 15 years ago and is now widely accepted amongst scientific community. The first neurotransmitter defect discovered in Alzheimer disease involved acetylcholine (ACh). As cholinergic function is required for short term memory, the cholinergic deficit in Alzheimer’s disease is also believed to be responsible for much of the short term memory deficit. The studies related to clinical trials of drugs in patients with Alzheimer disease have focused on the development of drugs augmenting the level of neurotransmitter acetylcholine in the brain in order to compensate for the loss of cholinergic function. Amongst these drugs, acetylcholine precursors, muscarinic agonists, nicotinic agonists and choline esterase inhibitors have extensively been studied in patients with Alzheimer’s disease and the successful approach to treat this disease have employed acetylcholineesterase (AChE) inhibition. The clinical response of few drugs namely donepezil (Aricept), rivastigmine (Exelon), galantamine (Reminyl) and Memantine (Nemenda) approved by Food and Drug Administration (FDA), USA for the treatment of Alzheimer’s disease, available presently, have been often found to be unsatisfactory. The presently available drugs for the treatment of Alzheimer’s disease are symptomatic only and do not alter the course or progression of the underlying disease and produce adverse reactions in patients thereby having limited scope for the treatment of patients of Alzheimer’s syndrome. Thus, there is need to develop targeted effective therapeutics for the treatment of Alzheimer’s disease which may alter the course or progression of the underlying disease by preventing the formation or clearing of plaques (beta-amyloid fragments), considered to be one hallmark of the disease, from the brain of the patients. There are several studies and alternative therapies which offer ways to slow the onset and progression of Alzheimer's disease in some patients. Various treatments can be used as preventive measures for people whose families have a history of the disease that indicate unique role of herbal medicine in the treatment of Alzheimer’s disease. Herbal remedies for Alzheimer’s disease have become more and more popular in the recent years and not without a reason that there is a possibility to slow down the brain’s degeneration caused by Alzheimer’s with natural treatments and it has drawn the attention of the scientific community. Many natural herbal treatments have been researched and the benefits derived from using herbal treatments for Alzheimer’s and dementia have been very promising. This paper reviews the clinical effects of a number of commonly used herbal medicines for the treatment of Alzheimer’s disease and dementia.